Trefoil peptide TFF2 (spasmolytic polypeptide) potently accelerates healing and reduces inflammation in a rat model of colitis. Issue 5 (1st May 1999) - Tran, C P; Cook, G A; Yeomans, N D; Thim, L; Giraud, A S
Abstract : BACKGROUND: The trefoil peptides are major secretory products of mucus cells of the gastrointestinal tract and show increased expression after inflammatory or ulcerative damage. Recombinant human TFF2 (spasmolytic polypeptide) has been shown to be cytoprotective, and enhances repair in models of gastric injury. AIMS: To test the healing effects of recombinant human (h)TFF2 in a rat model of chronic colitis. METHODS: Colitis was induced by intracolonic administration of dinitrobenzene sulphonic acid in ethanol. Mucosal repair was quantified macroscopically, microscopically by image analysis of tissue histology, and by measuring myeloperoxidase activity. RESULTS: Initial validation studies showed that maximal injury and inflammation occurred at the end of the first week after colitis induction (active phase), and that spontaneous healing was complete by eight weeks. Once daily intrarectal application of hTFF2 (2.5 mg/kg; approximately 0.5 mg/rat) for five days after maximal damage had been sustained, reduced both microscopic and macroscopic injury by 80% and inflammatory index by 50% compared with vehicle controls. In addition, endogenous concentrations of rat TFF2 and TFF3 (intestinal trefoil factor) were increased in the active phase of colitis and were reduced to basal levels by hTFF2 treatment. CONCLUSIONS: This study has shown that hTFF2 enhances the rate of colonic epithelial repair, and reduces local inflammation in a rat model of colitis, and suggests that luminal application of trefoil peptides may have therapeutic potential in the treatment of inflammatory bowel disease.